Detection of Atrial Fibrillation After Central Retinal Artery Occlusion. Issue 9 (7th June 2021) - Mac Grory, Brian; Landman, Sean R.; Ziegler, Paul D.; Boisvert, Chantal J.; Flood, Shane P.; Stretz, Christoph; Madsen, Tracy E.; Reznik, Michael E.; Cutting, Shawna; Moore, Elizabeth E.; Hewitt, Hunter; Closser, James B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Central retinal artery occlusion (CRAO) causes sudden, irreversible blindness and is a form of acute ischemic stroke. In this study, we sought to determine the proportion of patients in whom atrial fibrillation (AF) is detected by extended cardiac monitoring after CRAO. Methods: We performed a retrospective, observational cohort study using data from the Optum deidentified electronic health record of 30.8 million people cross-referenced with the Medtronic CareLink database of 2.7 million people with cardiac monitoring devices in situ. We enrolled patients in 3 groups: (1) CRAO, (2) cerebral ischemic stroke, and (3) age-, sex-, and comorbidity-matched controls. The primary end point was the detection of new AF (defined as ≥2 minutes of AF detected on a cardiac monitoring device). Results: We reviewed 884 431 patient records in common between the two databases to identify 100 patients with CRAO, 6559 with ischemic stroke, and 1000 matched controls. After CRAO, the cumulative incidence of new AF at 2 years was 49.6% (95% CI, 37.4%–61.7%). Patients with CRAO had a higher rate of AF than controls (hazard ratio, 1.64 [95% CI, 1.17–2.31]) and a comparable rate to patients with stroke (hazard ratio, 1.01 [95% CI, 0.75–1.36]). CRAO was associated with a higher incidence of new stroke compared with matched controls (hazard ratio, 2.85 [95% CI, 1.29–6.29]). Conclusions: The rate of AF detection after CRAO is higher than that seen in age-, sex-, and comorbidity-matched controls and comparable to that seen after ischemic cerebral stroke. Paroxysmal AF should be considered as part of the differential etiology of CRAO, and those patients may benefit from long-term cardiac monitoring.